Project-oriented training experience in micro-robot programming in college and its features - Talant Tolganbaiuly, Ainash Haliullinovna Davletova,; Tazhigulova, Almira Izbasarovna; Akmaral Hamzievna Kasymova, Laura Amangeldievna Smagulova,; Baigozhanova, Dametken Sagidullaevna (Opción, 2019)
In this article, a pedagogical experiment was conducted using a project-oriented training methodology to study about micro-robot programming at the Faculty of Information Technologies in college and its features. The research results show that the considered project-oriented teaching method allows one to fulfill teaching tasks through the example of various applied tasks, is effective in teaching micro-robot programming, and contributes to the development of creative abilities and communication skills in students. In conclusion, the participants have formed a holistic view of the project, while awareness of the completeness and significance of their activities increased the students’ self-esteem.